2017
DOI: 10.1364/ao.56.008492
|View full text |Cite
|
Sign up to set email alerts
|

Temperature characterization of a radiating gas layer using digital-single-lens-reflex-camera-based two-color ratio pyrometry

Abstract: The two-color ratio pyrometry technique using a digital single-lens reflex camera has been used to measure the time-averaged and path-integrated temperature distribution in the radiating shock layer in a high-enthalpy flow. A 70 mm diameter cylindrical body with a 70 mm long spike was placed in a hypersonic shock tunnel, and the region behind the shock layer was investigated. The systematic error due to contributions from line emissions was corrected by monitoring the emission spectrum from this region using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Emission spectroscopy performed in our shock tunnel also confirmed that the shock region majorly radiates as a continuous broadband source. After accounting for the spectro meter's instrument broadening, contribution from discrete line emissions due to impurities such as Na and Fe to the overall radiation intensity from the tunnel was found to be negligibly small [19]. As a result, measuring the temperature based on the broadband radiation from the soot particles due to paper and metal diaphragms, as well as from the dust particles, assuming the shock layer to be a gray-body source, would provide an indication of the conditions prevailing inside the shock tunnel.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Emission spectroscopy performed in our shock tunnel also confirmed that the shock region majorly radiates as a continuous broadband source. After accounting for the spectro meter's instrument broadening, contribution from discrete line emissions due to impurities such as Na and Fe to the overall radiation intensity from the tunnel was found to be negligibly small [19]. As a result, measuring the temperature based on the broadband radiation from the soot particles due to paper and metal diaphragms, as well as from the dust particles, assuming the shock layer to be a gray-body source, would provide an indication of the conditions prevailing inside the shock tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…Although the TCRP technique has been put to use in a variety of applications involving temperature measurement of radiating solid bodies or soot particles in fuel combustion [16][17][18], it was never used for shock-layer temperature characterization in short-duration facilities until recently. Deep et al [19] measured the temperature distribution within the radiating shock layer of a cylindrical body with spike using a commercial digital single lens reflex (DSLR) camera as the detector. Experiments were accomplished in a free-piston-driven shock tunnel (FPST): a ground testing impulse facility capable of simulating high-enthalpy hypersonic flow in its test section.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of applying dual-color thermography to plasma wind tunnel tests, it was demonstrated by De Cesare et al[64] with an aluminum alloy square plate as a target along with thermocouple measurements for comparison. Recently TCRP has been applied, using a DSLR camera, to measure the temperature distribution in the shock layer over the test model in a hypersonic shock tunnel (HST3) at the Laboratory for Hypersonic and Shock Wave Research (LHSR), Indian Institute of Science[65]. CHAPTER 3.…”
mentioning
confidence: 99%